The Impact of Technological Progress on Employee Engagement - Yang, Rong (Journal of Economics, Assets, and Evaluation, 2025)
This study investigates the multifaceted impact of technological progress on employee engagement within China’s rapidly evolving wine industry, focusing on key regions including Ningxia, Xinjiang, Shandong, and Southwest China. By integrating Self-Determination Theory (SDT), Conservation of Resources (COR) theory, and Socio-Technical Systems Theory, the research explores how automation, IoT, and AI adoption influence engagement across viticulture, winemaking, and sales roles. A sequential mixed-methods design combined quantitative surveys (N=300 employees) with qualitative interviews (N=15). Findings reveal a curvilinear relationship between automation and engagement: moderate automation (50–70%) enhances competence and autonomy, while excessive automation triggers skill displacement anxiety. Technological overload, particularly among older workers, was mitigated by organizational interventions (e.g., peer mentoring). The study bridges theoretical gaps in technology-engagement literature and offers practical strategies for optimizing human-machine synergy during digital transformation.